Investigation of the effect of lattice thermal conductivity on the thermoelectric performance of ScN monolayer. (September 2022) - Vahedi Fakhrabad, Davoud; Yeganeh, Mahboubeh
Abstract: In this work, the lattice thermal conductivity and thermoelectric properties of the ScN monolayer were investigated by density functional theory in combination with Boltzmann transport theory. The lattice thermal conductivity was 20.15 Wm −1 K −1 at 150 K which decreased to 4.54 Wm −1 K −1 at 800 K. The obtained thermoelectric performance by calculating the dimensionless figure of merit ZT is significantly influenced by temperature and doping concentration. Considering the lattice thermal conductivity for the calculation of ZT leads to a noticeable decrease of ZT particularly at low temperature; however, it was estimated that upon doping, the ZT can be improved. The highest ZT at T = 800 K and in the p-type and n-type regions was observed when the hole and electron concentrations of 2.38 × 10 13 and 5.86 × 10 12 cm −2 are considered, respectively.